2011
DOI: 10.1016/j.joca.2011.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Deformational behaviour of knee cartilage and changes in serum cartilage oligomeric matrix protein (COMP) after running and drop landing

Abstract: In vivo exercise interventions differentially regulate serum COMP concentrations and knee cartilage deformations. The relation between changes in COMP and in cartilage volume seems to depend on both mechanical and biochemical factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
102
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(120 citation statements)
references
References 54 publications
15
102
3
Order By: Relevance
“…Previous studies have shown that 30 minutes of one-legged knee extension exercise decreases synovial fluid COMP in osteoarthritic knees (Helmark et al, 2012). Furthermore, the knee state and type of exercise impact alterations in COMP levels, as in healthy knees serum COMP levels correlate with cartilage volume changes after drop landing but not after running (Niehoff et al, 2011). PGE2 is also increased in osteoarthritic synovial fluid (Nishimura et al, 2002) and is mechanically regulated in cartilage, as well as meniscus (Fermor et al, 2002; Hennerbichler et al, 2007; Waters et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that 30 minutes of one-legged knee extension exercise decreases synovial fluid COMP in osteoarthritic knees (Helmark et al, 2012). Furthermore, the knee state and type of exercise impact alterations in COMP levels, as in healthy knees serum COMP levels correlate with cartilage volume changes after drop landing but not after running (Niehoff et al, 2011). PGE2 is also increased in osteoarthritic synovial fluid (Nishimura et al, 2002) and is mechanically regulated in cartilage, as well as meniscus (Fermor et al, 2002; Hennerbichler et al, 2007; Waters et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…As discussed earlier, levels of COMP have been shown to increase with exposure to diverse forms of physical exercise (Kim et al 2007(Kim et al , 2009Niehoff et al 2010;Niehoff et al 2011). Given this evidence, COMP levels were expected to increase with exposure to the current flexion/extension task.…”
Section: Discussionmentioning
confidence: 79%
“…Given this evidence, COMP levels were expected to increase with exposure to the current flexion/extension task. However, these prior studies using COMP did not implement high levels of control over the areas of cartilage being stressed, for example involving marathon and other running tasks (Kim et al 2007(Kim et al , 2009Niehoff et al 2010) and drop landings (Niehoff et al 2011), while the current experiment was specifically designed to (at least partially) isolate the task to the lower back region. It is therefore possible that systemic COMP Table 1 MANOVA results for the effects of time (T), external load (L), and frequency (F) on COMP, IL6, and CK actual levels (AL) and change scores (CS).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to determine potential changes in cartilage response in the elderly due to the motor task reorganization, serum levels of cartilage oligomeric matrix protein (COMP) as a biomarker of cartilage metabolism were analyzed after a controlled incline walking exercise on the treadmill. COMP is currently being studied as a serum marker for cartilage degeneration in OA and knee joint disease [16], [17], and its serum level increases with cyclic mechanical loading [18], [19], [20]. Therefore, we additionally aimed to test the hypothesis that the consequences of the lower ambulatory knee joint loading in the elderly after the improvement of the TS and QF MTU capacities would influence cartilage metabolism by decreasing the serum COMP concentration after the cyclic loading exercise.…”
Section: Introductionmentioning
confidence: 99%